Про ізотопи груп. III - Сохацький, Ф.М. (Український математичний журнал, 1996)
We describe normal congruences of group isotopes, establish criteria of homomorphism and isomorphism, and select the methods for description of isotopes up to isomorphism. In addition, we establish a criterion for a subset to be a subquasigroup of a group isotope and describe subquasigroups of certain classes of group isotopes. The obtained results are applied to the investigation of left distributive quasi-groups. Встановлено критерій гомоморфізму, описано нормальні конгруентності ізотопів груп. Знайдено критерій ізоморфізму, виділено методи опису ізотопів з точністю до ізоморфізму. Виділено підмножини, які є підквазігрупами групового ізотопу. Описано підквазігрупи деяких класів групових ізотопів. Одержані результати застосовано до вивчення ліводистрибутивних квазі-груп.